PENGARUH KEPUASAN PASIEN TENTANG PELAYANAN KEBIDANAN TERHADAP PEMANFAATAN PELAYANAN KESEHATAN DI PUSKESMAS PONTAP TAHUN 2016 - Devi Darwin; Ny. Irmayanti; Tirta Nirwana (Lembaga Penerbit dan Publikasi Ilmiah (LPPI) Universitas Muhammadiyah Palopo, 2017)
Satisfaction is formed from a result and a comparative reference, comparing the results received with a particular standard. The comparison forms three possibilities: first is if the service is perceived to be above the expectation (quality surprise), the second when the quality of service fulfills the expectation, and the last if the service received is worse than the expected service.The influence of physical needs in patient satisfaction on the utilization of health service shows that from 89 respondents, respondents who have good physical needs about patient satisfaction on utilization of health services as much as 43 respondents and respondents who need less physical as much as 46 respondents. Based on the result of statistical test analysis, it is said that there is influence of physical requirement in patient satisfaction to health service utilization. Keywords: Satisfaction, Midwifery Services